2005
DOI: 10.1038/sj.eye.6701630
|View full text |Cite
|
Sign up to set email alerts
|

Ocular findings in patients with solid tumours treated with the epidermal growth factor receptor tyrosine kinase inhibitor gefitinib (‘Iressa’, ZD1839) in Phase I and II clinical trials

Abstract: Purpose To describe the strategy used for large-scale ophthalmological monitoring in the clinical development of the novel anticancer agent gefitinib ('Iressa', ZD1839), an epidermal growth factor receptor tyrosine kinase inhibitor, which had demonstrated ocular effects in preclinical animal models. Methods In this extensive clinical trial programme, patients in Phase I and II trials underwent frequent and intensive ophthalmological monitoring at baseline and during the trials. Data were reviewed by an externa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 13 publications
1
34
0
1
Order By: Relevance
“…Tullo et al reviewed the ocular toxicity reported during three dose-escalating, multi-centre Phase I trials and in both IDEAL trials [57]. There were 221 patients in the Phase I trials.…”
Section: Ophthalmologic Effectsmentioning
confidence: 98%
“…Tullo et al reviewed the ocular toxicity reported during three dose-escalating, multi-centre Phase I trials and in both IDEAL trials [57]. There were 221 patients in the Phase I trials.…”
Section: Ophthalmologic Effectsmentioning
confidence: 98%
“…Overexpression and hyperactivation of the EGFR are associated with a number of cancers, including those of the lung, colon, and kidney (3). Conversely, attenuation of EGFR kinase activity in patients using pharmacological inhibitors such as Iressa or Tarceva has been reported to disrupt epithelial homeostasis, resulting in colitis, dermatitis, and corneal erosions (4,5). Thus, both too much or too little EGFR signaling can be deleterious.…”
mentioning
confidence: 99%
“…Mice that have been engineered to knock out the EGFR gene are either embryonic lethal or die shortly after birth, indicating its role in prenatal development (Miettinen et al, 1995;Sibilia and Wagner, 1995;Threadgill et al, 1995). Patients taking EGFR inhibitors as part of an anti-cancer chemotherapeutic regimen, experience complications such as colitis, dermatitis, and corneal abrasions, indicating the receptor contributes to the homeostasis of those tissues (Tullo et al, 2005;Zhang et al, 2007). This is supported by the genetically engineered deletion of EGFR ligands (i.e.…”
Section: The Egfrmentioning
confidence: 74%